Олеснување на трговијата во современиот мултилатерален трговски систем - Тошевска Трпчевска, Катерина (Економски факултет, УКИМ, Скопје, 2012)
Trade facilitation is important concept for increasing the international trade liberalization. This concept understands the reduction of informal and administrative barriers that have negative effects over international trade in goods. The losses and costs that companies have because of border crossings waiting, insufficient transparency and predictability of trade procedures, massive documentation and application of old and lengthy customs procedures are slowing down international trade flows. In the negotiation framework of the World Trade Organization trade facilitation is the field were consensus can be easily reached among the countries in the world. With the eventual successful completion of the trade negotiations biggest positive effects over trade and national income are expected to be realized from implementing trade facilitation measures for all countries in the world. Another international organization working in the field of trade facilitation is the World Customs Organization. This organization is preparing and developing standards for implementing trade facilitation measures for increasing customs efficiency and speeding up the flows of goods over border crossings. Republic of Macedonia is small, import dependent and landlocked country whose export products should cross several borders to reach the biggest and most important trade destination, the European market. Undertaking trade facilitation measures and measures for increasing the customs efficiency is essential for Republic of Macedonia and her neighboring countries because positive effects can be realized by the country implementing the measures and the countries that are her trading partners. The goal of this paper is to summarize the effects of the implementation of certain trade facilitation measures in the Republic of Macedonia and their influence over facilitating and speeding up trade. Subject of research are simplified customs procedures and the single window concept for issuing import, export and transit licenses. In the research an attempt is made to see the readiness of Macedonian companies to implement the authorized economic operator concept which is one of the latest solutions of the international trade community to facilitate global trade. The readiness of Macedonian companies is measured through comparison of the costs needed to implement the necessary conditions for the authorized status and the possible benefits from the trade facilitation measures.
Trade facilitation in the contemporary multilateral trading system
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Ирена Кикеркова.
Keywords: trade facilitation, World Trade Organization, World Customs Organization, Republic of Macedonia, authorized economic operator